Site selection by geese in a suburban landscape - Groom, Quentin J; Adriaens, Tim; Colsoulle, Claire; Delhez, Pauline; Van Der Beeten, Iris (PeerJ Preprints, 2019)
Background In northern European and North American cities geese are one of the commonest and most visible large herbivores that inhabit the suburban environment . As such, their presence and behavior often conflicts with the desires of the human residents. Fouling, noise, aggression and health concerns are all cited as reasons that there are “too many”. Lethal control is often used for control, however, this raises questions about whether this is a sustainable strategy to resolve the conflict between humans and geese, when paradoxically, it is humans that are responsible for creating the habitat and often providing the food and protection of geese at other times. We hypothesis that the landscaping of suburban parks can be improved to decrease its attractiveness to geese and to reduce the opportunity for conflict between geese and humans. Methods. Using observations collected over five years from a botanic garden situated in suburban Belgium and data from the whole of Flanders in Belgium we examine landscape features that attract geese, including the presence of islands in lakes, the distance from water, barriers to level flight and the size of grazing areas. The birds studied were the tadornine goose Alopochen aegyptiaca (L. 1766) (Egyptian geese) and the anserine geese, Branta canadensis (L. 1758) (Canada geese), Anser anser (L. 1758) (greylag geese) and Branta leucopsis (Bechstein, 1803) (barnacle geese). Landscape modification is a known method for modifying geese behavior, but there is little information on the power of such methods with which to inform managers and planners. Results. Our results demonstrate that lakes with islands attract more than twice as many anserine geese, than lakes without island, but make little difference to Egyptian geese. Furthermore, flight barriers between grazing areas and lakes are an effective deterrent to geese using an area for feeding. Keeping grazing areas small and surrounded by trees reduces their attractiveness to geese. Conclusion. The results suggest that landscape design can be used successfully to reduce the number of geese and their conflict with humans. However, this approach has its limitations and would require humans to compromise on what they expect from their landscaped parks, such as open vistas, lakes and closely cropped lawns.
Keywords: invasive; feral; habitat; behavior; Belgium; Alopochen aegyptiaca; Branta canadensis; Anser anser; Branta leucopsis; lakes